1999
DOI: 10.1086/302621
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New Locus for Generalized Epilepsy with Febrile Seizures Plus (GEFS+) on Chromosome 2q24-q33

Abstract: We report the identification of a new locus for generalized epilepsy with febrile seizures plus (GEFS+). Six family members manifested isolated typical febrile seizures (FS), and five had typical FS associated with generalized epilepsy (FS+, generalized tonic/clonic seizures). Afebrile seizures occurred from childhood until the teenage years. The maximum two-point LOD score was 3.99 for markers D2S294 and D2S2314. Flanking markers place the GEFS+ locus between D2S141 and D2S116, with multipoint analysis favori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
1
7

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 21 publications
3
70
1
7
Order By: Relevance
“…These, therefore, suggest that other genes might also be involved in GEFSϩ and FS associated with afebrile seizures. The chromosomal locus 2q24, in which GEFSϩ has been mapped, harbors not only Na v 1.1 but also other ␣-subunits including Na v 1.2 (SCN2A) (10,(13)(14)(15). Given that Na v 1.2 is also expressed in high levels in the central nervous system with a tissue-specific profile (16), Na v 1.2 is an intriguing candidate.…”
mentioning
confidence: 99%
“…These, therefore, suggest that other genes might also be involved in GEFSϩ and FS associated with afebrile seizures. The chromosomal locus 2q24, in which GEFSϩ has been mapped, harbors not only Na v 1.1 but also other ␣-subunits including Na v 1.2 (SCN2A) (10,(13)(14)(15). Given that Na v 1.2 is also expressed in high levels in the central nervous system with a tissue-specific profile (16), Na v 1.2 is an intriguing candidate.…”
mentioning
confidence: 99%
“…In 1999, linkage analysis in 2 large families localized a second GEFS+ locus to an interval of chromosome 2q24 that includes a sodium channel gene cluster (12,13). Sequencing of SCN1A demonstrated that affected individuals are heterozygous for missense mutations in highly evolutionarily conserved amino acid residues, T875M in 1 family and R1648H in the other (14).…”
Section: Inherited and De Novo Mutations Of Scn1a In Gefs+ Severe Myomentioning
confidence: 99%
“…A second locus, GEFS+2, was mapped in 1999 to a 20-cM interval of chromosome 2q24 that contained the α subunit genes SCN1A, SCN2A, and SCN3A by analysis of two large families (6,50). Screening affected individuals from both families using conformation sensitive gel electrophoresis of amplified exons identified two missense mutations in the SCN1A gene, R1648H and T875M (27).…”
Section: Generalized Epilepsy With Febrile Seizures Plus-mentioning
confidence: 99%